Photoprotective activity of extracts from the five lichen species against human keratinocyte (HaCАT) - Khramchankova, Volga M.; Matveyenkau, Matsvei V. (Journal of the Belarusian State University. Ecology, 2019)
In vitro, the photo-protective properties of ethanol extracts from the widely distributed in Belarus lichens Hypogymnia physodes, Evernia prunastri, Ramalina pollinaria, Xanthoria parietina and Cladonia arbuscula in the culture of human keratinocytes (HaCAT), are estimated. The SPF extracts from E. prunastri and R. pollinaria possess very high photoprotective properties; extracts from H. physodes and C. arbuscula – high; X. parietina – low. According to SPF, λcrit and UV-A / UV-B ratio, ethanol extract from C. arbuscula is sunscreen with characteristics for the level of photoprotection «high» and «maximum». An in vitro modification with extracts from lichens of the sensitivity of human keratinocytes (HaCAT) to ultraviolet irradiation has been established. Extracts from R. pollinaria and C. arbuscula reduced the halflethal dose by 1.6–2.0 times, extracts from H. physodes, E. prunastri, and X. parietina were increased by 1.4 to 1.6 times. With increasing doses of irradiation of keratinocytes by ultraviolet to lethal values, extracts from R. pollinaria were photoprotectors, their activity increased with increasing concentration. Extracts from C. arbuscula in concentrations of 2.5 ÷ 5.0 μg/ml also showed photoprotective properties, and suppressed the vital activity of keratinocytes at concentrations close to semi-inhibitory. Extracts from H. physodes, E. prunastri and X. parietina showed moderate sensitization properties.